PENGARUH PENGGUNAAN MODEL PEMBELAJARAN KOOPERATIF TIPE TGT DAN MEDIA ELEKTRONIK EDUCAPLAY TERHADAP HASIL BELAJAR MATEMATIKA SISWA KELAS V MIS AL BASHIRAH KOTA MAKASSAR - Syamsuriawati, A.; Faisal, Muhammad; Pada, Amir (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study is an experimental research aimed at determining the effect of the use of the Teams Games Tournament (TGT) cooperative learning model and electronic media Educaplay on the mathematics learning outcomes of fifth-grade students at MIS Al Bashirah Makassar City. This study employed a quantitative approach with an experimental research design. The research design used was a quasi-experimental design in the form of a non-equivalent control group design. The population of this study consisted of 90 students, with samples from class VD (24 students) and class VC (23 students). Data collection techniques were carried out through teacher observation and learning outcome tests in the form of pretest and posttest. Data analysis used descriptive and inferential statistical analysis. The results of the study obtained are: 1) The use of the TGT model was categorized as very good; 2) The use of Educaplay electronic media was also categorized as very good; 3) The mathematics learning outcomes of students in the experimental class were in the high category; and 4) There was an effect of using the TGT-type cooperative learning model and Educaplay electronic media on the mathematics learning outcomes of fifth-grade students at MIS Al Bashirah Makassar City.